Subcutaneous Thyroid Tissue Implantation after Thyroidectomy: A Mimic of Benign Cutaneous Tumours - Itsuki Takei; Takamichi Ito; Taro Mori; Yoshinao Oda; Takeshi Nakahara (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)